(untitled) (Scientific journal of the Fergana State University, 2024)
Currently, morphological characters play an important role as the most important diagnostic characters in plant taxonomy. This is especially important when studying the diversity of taxa belonging to the Lamiaceae family, which is widespread on Earth. The diagnostic characters of the taxa of this family were first divided into 4 groups according to the classification of characters developed for the family by A.Makhmedov (1991). These are: generic characters, sectional characters, species characters, intraspecific characters. These diagnostic characters are especially important in the taxonomy of species of this family. An important feature is the fact that the stems of the Lamiaceae family are tetrahedral. However, in some taxa of the genus Salvia belonging to this family, we can see that the stem is hexagonal.